CLOCK/BMAL1 regulates circadian change of mouse hepatic insulin sensitivity by SIRT1. Issue 6 (25th April 2014) - Zhou, Ben; Zhang, Yi; Zhang, Fang; Xia, Yulei; Liu, Jun; Huang, Rui; Wang, Yuangao; Hu, Yanan; Wu, Jingxia; Dai, Changgui; Wang, Hui; Tu, Yanyang; et al.
<x xml:space="preserve">Abstract</x> The protein deacetylase, sirtuin 1 (SIRT1), involved in regulating hepatic insulin sensitivity, shows circadian oscillation and regulates the circadian clock. Recent studies show that circadian misalignment leads to insulin resistance (IR); however, the underlying mechanisms are largely unknown. Here, we show that CLOCK and brain and muscle ARNT‐like protein 1 (BMAL1), two core circadian transcription factors, are correlated with hepatic insulin sensitivity. Knockdown of CLOCK or BMAL1 induces hepatic IR, whereas their ectopic expression attenuates hepatic IR. Moreover, circadian change of insulin sensitivity is impaired in Clock mutant, liver‐specific Bmal1 knockout (KO) or Sirt1 KO mice, and CLOCK and BMAL1 are required for hepatic circadian expression of SIRT1. Further studies show that CLOCK/BMAL1 binds to the SIRT1 promoter to enhance its expression and regulates hepatic insulin sensitivity by SIRT1. In addition, constant darkness‐induced circadian misalignment in mice decreases hepatic BMAL1 and SIRT1 levels and induces IR, which can be dramatically reversed by resveratrol. Conclusion: These findings offer new insights for coordination of the circadian clock and metabolism in hepatocytes by circadian regulation of hepatic insulin sensitivity via CLOCK/BMAL1‐dependent SIRT1 expression and provide a potential application of resveratrol for combating circadian misalignment‐induced metabolic disorders. (Hepatology 2014;59:2196–2206)